Hubungan Antara Kepemimpinan Dengan Kinerja Pustakawan di Taman Baca Masyarakat Kecamatan Gubeng Surabaya - Siti Anis Wijayanti (Tafkir: Interdisciplinary Journal of Islamic Education, 2020)
This study aims to determine whether there is a relationship between leadership and librarian performance. The population in this study were all staff / librarians from all Gubeng sub-districts, consisting of 27 people from 26 Community Reading Gardens and 26 Schools in Gubeng District. The results of the data analysis show that there is a positive and significant relationship between leadership and librarian performance with the results of t count greater than t table (2.2651> 2.101).